Perspectives of Parents on Communication Challenges Faced in Educating Learners with Hearing Impairments - Ogada, Rosemary (2019)
Focusing on Education Policy for Deaf Children, the World Federation o f the Deaf (WFD, 2016) postulated that children with HI have a right t o full access to quality education and that since persons with hearing impairments (HI) are mainly visual, sign language and visual strategi es must be availed to learners with HI as a birthright. This may be in terpreted to mean that if quality education is not availed to learners with HI using visual strategies and in sign language, the policies la id down by WFD would have been contravened. It can also be implied tha t sign language needs to be availed to learners with HI at home with p arents, siblings and care givers where they grow and learn before goin g to school. The purpose of this study was therefore to establish the perspectives of parents on communication challenges faced in educating learners with hearing impairments in. This study adopted a case study research design using a qualitative research approach and was informe d by the Social Model of Disability as propagated by Union of Physical ly Impaired Against Segregation (UPIAS) (1976). The objective of the s tudy was to establish the perspectives of parents on communication cha llenges faced in educating learners with hearing impairments. The targ et population was 177 comprising 150 parents of learners with hearing impairments, 26 teachers and 1 Quality Assurance and Standards Officer . The study employed purposive sampling technique to sample 30 parents and 13 teachers while saturated sampling technique was used to for 1 Quality Assurance and Standards Officer (QUASO). Data was collected by use of interview schedules, focus group discussion guides and documen t analysis guides. Trustworthiness was established by use of detailed report of the process within the study, member checks and overlapping methods. Data was analyzed using thematic analysis technique as propos ed by Braun and Clarke (2006). The study established that most parents of learners with hearing impairments held the view that sign language was too difficult to learn at their age though they expected the scho ol and the government to facilitate sign language trainings for them. This study concluded that communication between parents and their chil dren was ineffective because parents viewed themselves as unable to le arn sign language and communication between parents and the school was ineffective because most parents viewed the teachers as disorganized in the way they communicated with parents. Keywords: Hearing impairmen ts, communication, parents, learners, challenges, educating learners w ith HI DOI : 10.7176/JEP/10-3-04